Hepatitis A virus in urban sewage from two Mediterranean countries - PINTÓ, R. M. (Cambridge University Press, 2007)
Molecular methods for the detection and typing of hepatitis A virus (HAV) strains in sewage were applied to determine its distribution in Cairo and Barcelona. The study revealed the occurrence of different patterns of hepatitis A endemicity in each city. The circulating strains characterized, whether in Cairo or Barcelona, were genotype IB. The effects of a child vaccination programme and the increase in the immigrant population on the overall hepatitis A occurrence in Barcelona were evaluated. While vaccination contributed to a significant decrease in the number of clinical cases, the huge recent immigration flow has probably been responsible for the re-emergence of the disease in the last year of study, in the form of small outbreaks among the non-vaccinated population.